1999
DOI: 10.1038/16927
|View full text |Cite|
|
Sign up to set email alerts
|

In vivo regulation of axon extension and pathfinding by growth-cone calcium transients

Abstract: Growth cones at the tips of extending neurites migrate through complex environments in the developing nervous system and guide axons to appropriate target regions using local cues. The intracellular calcium concentration ([Ca2+]i) of growth cones correlates with motility in vitro, but the physiological links between environmental cues and axon growth in vivo are unknown. Here we report that growth cones generate transient elevations of [Ca2+]i as they migrate within the embryonic spinal cord and that the rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
338
2
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 453 publications
(356 citation statements)
references
References 25 publications
15
338
2
1
Order By: Relevance
“…The role of increases of the cytosolic calcium concentration in controlling cell motility has been reported in various cell types ranging from fibroblasts to immature neurons [39,40]. Neuronal precursors and post-migratory neurons in the fetal cerebrum and the early postnatal cerebellum exhibit spontaneous Ca 2+ transients [41,42], suggesting that the role of Ca 2+ transients in development may be constantly remodelled by internal programs and extracellular cues.…”
Section: Discussionmentioning
confidence: 99%
“…The role of increases of the cytosolic calcium concentration in controlling cell motility has been reported in various cell types ranging from fibroblasts to immature neurons [39,40]. Neuronal precursors and post-migratory neurons in the fetal cerebrum and the early postnatal cerebellum exhibit spontaneous Ca 2+ transients [41,42], suggesting that the role of Ca 2+ transients in development may be constantly remodelled by internal programs and extracellular cues.…”
Section: Discussionmentioning
confidence: 99%
“…Possible effects of calcium are intriguing as it is involved in several adhesion-related events in the central nervous system: Ca 2+ affects the conformation, aggregation and refolding transitions of ependymin (a cell-adhesion related molecule associated in neural plasticity) (Ganss and Hoffmann, 1993). Also Ca 2+ binding to sialic acids facilitates fibrinogen monomer aggregation in fibrin assembly (Dang et al, 1989) and Ca 2+ transients were shown to control in vivo regulation of axon extension and growth-cone path finding (Gomez and Spitzer, 1999)-a phenomenon also associated with NCAM-PSA. Although the extra-cellular Ca 2+ concentration in brain is normally low, local concentrations may differ by several orders of magnitude due to gradients, mirroring intracellular transients (Nicholson, 1980).…”
Section: As Well As In Capsularmentioning
confidence: 99%
“…Calcium entry is also shown to regulate NCAM isoform expression and polysialylation in the developing muscle (Rafuse and Landmesser, 1996). Interestingly, the polysialic acid moiety of the NCAM was recently shown to be involved in the guidance of retinal axons (Monnier et al, 2001), an event also controlled by Ca 2+ (Gomez and Spitzer, 1999). As a hygroscopic salt, Ca 2+ could double the effective hydration volume of PSA-a property that is considered sufficient to explain the role of PSA in NCAM function (Troy, 1992).…”
Section: Divalent Cationsmentioning
confidence: 99%
“…Calcium signaling has an effect on the growth rate of growth cones, first characterized as a narrow extracellular calcium concentration range favorable for growth [43,[60][61][62]. Surprisingly, calcium transients [63,64] and calcium entry through mechanosensitive channels slow axon growth, whereas calcium release from ER stores enhances growth [41].…”
Section: Reviewmentioning
confidence: 99%